Analisis kesalahan Diksi dan Kalimat dalam Surat Dinas pada Kantor Wali Kota Makassar Provinsi Sulawesi Selatan - M. Asri B. (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
Aspects of language in official letter is a very vital thing. It’s possible because through language, important official information can be well achieved. Therefore, the language in the official letters needs to be organized in such a way. The method used in this research was descriptive analytical method with documentation technique. The purpose of this study was to describe the forms of diction and sentences errors in official letters in Makassar’s Mayor Office. The results obtained were the findings of thirteen errors of language comprising six forms of diction errors together with seven forms of sentence errors.